2023
DOI: 10.1002/adbi.202300097
|View full text |Cite
|
Sign up to set email alerts
|

Role of Telomeres and Telomerase in Parkinson's Disease—A New Theranostics?

Balachandar Vellingiri,
Kiruthika Balasubramani,
Mahalaxmi Iyer
et al.

Abstract: Parkinson's disease (PD) is a complex condition that is significantly influenced by oxidative stress and inflammation. It is also suggested that telomere shortening (TS) is regulated by oxidative stress which leads to various diseases including age‐related neurodegenerative diseases like PD. Thus, it is anticipated that PD would result in TS of peripheral blood mononuclear cells (PBMCs). Telomeres protect the ends of eukaryotic chromosomes preserving them against fusion and destruction. The TS is a normal proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 155 publications
0
0
0
Order By: Relevance
“…A study conducted by Scheffold et al in a PD mouse model with telomere shortening phenotype (TERC knockout) indicated that earlier onset of synuclein aggregation had taken place with documented defective microglial immune response in the aged brain [ 39 ]. Thus, the study introduces the contribution of microglia telomere attrition in PD pathogenesis and adds to the hypothesis that telomere erosion with aging may be a risk factor in neurodegenerative disorders [ 40 ].…”
Section: The Role Of Microglia Telomere Shortening In Parkinson’s Dis...mentioning
confidence: 99%
“…A study conducted by Scheffold et al in a PD mouse model with telomere shortening phenotype (TERC knockout) indicated that earlier onset of synuclein aggregation had taken place with documented defective microglial immune response in the aged brain [ 39 ]. Thus, the study introduces the contribution of microglia telomere attrition in PD pathogenesis and adds to the hypothesis that telomere erosion with aging may be a risk factor in neurodegenerative disorders [ 40 ].…”
Section: The Role Of Microglia Telomere Shortening In Parkinson’s Dis...mentioning
confidence: 99%